2012
DOI: 10.1016/j.virol.2011.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of a novel putative mycovirus infecting the conifer root-rot fungus Heterobasidion annosum sensu lato

Abstract: We describe a novel putative mycovirus infecting the conifer root-rot fungus Heterobasidion annosum sensu lato. This virus, designated as Heterobasidion RNA virus 6 (HetRV6), is taxonomically distant from all previously known viruses of Heterobasidion species, but somewhat related to the Curvularia thermal tolerance virus and the Fusarium graminearum virus 4. Based on a population analysis including 35 virus strains from Heterobasidion abietinum, Heterobasidion parviporum, Heterobasidion annosum sensu stricto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 54 publications
2
91
2
Order By: Relevance
“…In this investigation, we show that Heterobasidion isolates at a forest site with a long history of root and butt rot had a viral infection rate of 48-67%, which was considerably higher than the typical 15-17% that was observed in earlier studies (Ihrmark, 2001;Vainio et al, 2012) and suggests that viruses accumulate over time in Heterobasidion clones. Our 7-year follow-up work also revealed the appearance of novel viral infections in aging clones.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…In this investigation, we show that Heterobasidion isolates at a forest site with a long history of root and butt rot had a viral infection rate of 48-67%, which was considerably higher than the typical 15-17% that was observed in earlier studies (Ihrmark, 2001;Vainio et al, 2012) and suggests that viruses accumulate over time in Heterobasidion clones. Our 7-year follow-up work also revealed the appearance of novel viral infections in aging clones.…”
Section: Discussioncontrasting
confidence: 59%
“…Four distinct viral species occurred at the sample plot: three putative members of Partitiviridae and the yet-to-be-assigned HetRV6 (Vainio et al, 2012). We found no indications of additional viral strains being present at the study plot, as the dsRNA patterns shown by CF11 chromatography agreed with the RT-PCR results and all dsRNA-positive isolates could be associated with one (or more) of these four viral species by RT-PCR.…”
Section: Virus Diversitymentioning
confidence: 48%
See 3 more Smart Citations